DAMPAK KRISIS GLOBAL TERHADAP LIKUIDITAS BANK DEVISA NASIONAL - Suharyono Suharyono (Inovbiz: Jurnal Inovasi Bisnis, 2015)
Abstract: The global crisis has led banks experienced liquidity problems. The measurement of banks' liquidity ratios is useful to assess the composite rating of a bank, as the impact of the global crisis toward the liquidity of foreign exchange banks. This study aimed to determine whether there was significant difference between the liquidity of foreign exchange banks before and after the global crisis. The Bank’s liquidity was measured using liquidity ratios by comparing current assets to current liabilities. The population of this study was 35 foreign exchange banks.  The  hypothesis  was  tested  by  using  Mann  Whitney  non-parametric different-test. The research of this study showed that the liquidity of foreign exchange  banks  before  and  during  global  crisis  had  a  significant  difference. While, the foreign exchange banks liquidity during and after the global crisis, and its liquidity before and after the global crisis did not have significant difference. Key words: Liquidity, bank, foreign exchange, crisis, global.